Evaluation of malnutrition risk screening in hospitalized children with digestive system diseases—a single-center cross-sectional study - Li, Xiaoyu; Zou, Yu; Zuo, Jing; Xu, Tian; Zeng, Huilin; Ou, Ruiju; Dai, Dongling (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to assess the malnutrition risk of hospitalized children with digestive system diseases and provide evidence for clinical nutritional support.MethodsIn this single-enter cross-sectional study, the modified pediatric malnutrition risk screening tool was used to assess the malnutrition risk of pediatric patients hospitalized for digestive system diseases from January 2024 to June 2024. The screening was carried out within 24 h after admission, and scores ≥4 and <4 were considered as high risk of malnutrition and non-high risk of malnutrition, respectively. We collected the data from all children, including age, gender, malnutrition risk, nutritional support, and clinical outcomes. SPSS software package (version 23.0) was used for data processing.ResultsA total of 1,200 children aged 1 month to 18 years were included in this study. The incidence of malnutrition risk in all hospitalized children was 53.17%, and the percentage of high malnutrition risk was 13.67%. There was a significant difference in the incidence of high malnutrition risk between different diseases (P < 0.01). The difference in nutritional support rate (P < 0.05) and outcomes (P < 0.05) was also significant in patients with different degrees of malnutrition risk.ConclusionsTimely, standardized, and comprehensive nutritional assessment is of crucial importance for reasonable nutritional interventions to improve clinical outcomes in children with high malnutrition risk.